A physical route to porous ethyl cellulose microspheres loaded with TiO2 nanoparticles. Issue 19 (30th April 2014) - Cai, Weiwei; Yang, Hui; Han, Daxin; Guo, Xingzhong
ABSTRACT Porous ethyl cellulose (EC) microspheres were prepared via a physical method in oil‐in‐water (O/W) emulsions. The morphologies and pore structures of the resulting porous microspheres were investigated by scanning electron microscopy (SEM), mercury porosimeter and spectrometer equipped with an integrating sphere. The increase of EC amount in oil phase will increase the size of the microspheres. All the microspheres possess open macropores in the shell and interconnected pores inside the microspheres by means of phase separation. The saturation of the Ethyl acetate (EA) in external phase has an effect on the morphology of the EC particles obtained. Using EA unsaturated aqueous solution as the external water phase in the emulsion process results in the formation of porous EC particles with irregular shape. The loaded TiO2 nanoparticles uniformly disperse in EC matrix, and slightly deceases the size and volume of interconnected pores inside the microspheres. The addition of TiO2 nanoparticles is also proved to increase the light‐scattering power of the porous EC microspheres. © 2014 Wiley Periodicals, Inc. J. Appl. Polym. Sci. 2014, 131, 40822.